Preparation method of high-performance coated AG glass

By spraying multi-layer functional solutions on the glass surface and optimizing the proportion, a composite nanonetwork structure is formed, which solves the problem of insufficient binding performance and performance of the existing AG glass coating layer, and achieves high-performance coated AG glass with high light transmittance, excellent anti-fog and solvent resistance.

CN119661091APending Publication Date: 2025-03-21SUZHOU ETONE MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411528274.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing spraying method for preparing AG glass has problems such as insufficient bonding performance between the coating coating and the glass substrate and the coating coating performance needs to be improved.

Method used

By spraying the base layer, intermediate layer and surface layer solutions on the glass surface in sequence, and optimizing the ratio of each functional layer, a composite nanonetwork structure is formed to improve the binding performance of the coating and the glass substrate and the anti-fog, solvent resistance and light transmission properties of the glass.

Benefits of technology

The light transmittance, anti-fog performance, adhesion, mechanical stability and solvent resistance of coated AG glass are significantly improved, and the overall performance of the glass is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005109826160000111
    Figure BDA0005109826160000111
  • Figure BDA0005109826160000121
    Figure BDA0005109826160000121
  • Figure BDA0005109826160000131
    Figure BDA0005109826160000131
Patent Text Reader

Abstract

The invention discloses a preparation method of high-performance coated AG glass. The preparation method comprises the following steps: preparing a bottom layer solution; preparing an intermediate layer solution; preparing a surface layer solution; the preparation method comprises the following steps: cleaning a glass substrate by adopting deionized water and isopropanol in sequence, then etching the glass substrate, placing the etched glass substrate in a bottom layer solution, carrying out first dip-coating treatment, taking out the etched glass substrate, placing the etched glass substrate in an intermediate layer solution, carrying out second dip-coating treatment, taking out the glass substrate, and calcining the glass substrate in a muffle furnace to obtain the high-strength glass substrate. Obtaining a glass plate with a bottom layer and a middle layer; the glass plate with the bottom layer and the middle layer is placed in the surface layer solution to be subjected to third dip-coating treatment, the glass plate is taken out and dried, and the high-performance coated AG glass is prepared. According to the invention, by spraying a plurality of functional layers on the surface of the glass and optimizing the ratio of the functional layers, the bonding performance of the coating and the glass substrate is effectively improved, and the antifogging performance, solvent resistance and light transmission of the glass are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thin film materials, and in particular to a method for preparing high-performance coated AG glass. Background Art

[0002] AG glass, also known as anti-reflective glass and anti-glare glass, is a kind of glass with special processing on the glass surface. Its characteristic is that the original reflective surface of the glass is changed into a matte non-reflective surface. The principle is that the double-sided or single-sided of the high-quality glass sheet is specially processed to make it have a lower reflectivity compared with ordinary glass. AG glass is mainly used in ATM machine displays, outdoor displays, electronic whiteboards, electronic blackboards, car displays, mobile phones, etc. It can prevent reflections and enable the content on the screen to be clearly seen under strong light, thereby reducing the interference of ambient light, improving the clarity of the picture, reducing screen reflections, making the image clearer and more realistic, and allowing viewers to enjoy better visual effects.

[0003] With the rapid development of science and technology, AG glass technology is also constantly improving and updating. The existing AG glass preparation methods mainly include physical processing, chemical processing, and spraying. The physical processing method is the process of spraying relatively small quartz sand or corundum on the glass surface to form a rough surface, or by frosting the glass surface to form an uneven rough surface. The chemical method mainly reacts with chemical substances and glass to generate insoluble fluorosilicates and deposit them on the surface of the glass to form insoluble ultrafine crystal particles. These ultrafine crystal particles densely cover the glass surface to prevent the chemical substances from further reacting with the glass, thereby forming non-uniform erosion and obtaining a translucent rough surface. . The spraying method is to evenly coat submicron silica and other particles on the glass surface in a clean environment, and then heat and solidify the glass to form a layer of particles on the glass surface, which diffusely reflects the light to achieve an anti-glare effect. In the above scheme, the spraying method has low cost, low requirements for the glass substrate, simple operation, and is widely used. However, there are still the following problems in preparing AG glass by the spray method: the bonding performance between the coating and the glass substrate needs to be further improved, and the performance of the coating needs to be further improved. Summary of the invention

[0004] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a method for preparing high-performance coated AG glass is provided, which effectively improves the bonding performance between the coating and the glass substrate by spraying multiple functional layers on the glass surface and optimizing the ratio of each functional layer, and effectively improves the anti-fog performance, solvent resistance and light transmittance of the glass.

[0005] In order to solve the above technical problems, the technical solution of the present invention is:

[0006] A method for preparing high-performance coated AG glass comprises the following steps:

[0007] S1: Preparation of bottom solution:

[0008] Mix ethyl orthosilicate, hydrochloric acid, deionized water and anhydrous ethanol, then add polyethylene glycol and stir to mix evenly to obtain a bottom solution;

[0009] S2: Preparation of intermediate layer solution:

[0010] Mixing tetraethyl orthosilicate, hydrochloric acid, deionized water and anhydrous ethanol to obtain a first solution, mixing ammonia monohydrate and anhydrous ethanol to obtain a second solution, mixing tetraethyl orthosilicate and anhydrous ethanol to obtain a third solution, slowly adding the third solution to the second solution to adjust the pH of the second solution to be neutral, and then adding the first solution to the second solution and mixing evenly to obtain an intermediate layer solution;

[0011] S3: Preparation of surface solution:

[0012] The tetraethyl orthosilicate, ethanol and deionized water are uniformly mixed, ammonia monohydrate is added, and a stirring reaction is performed to obtain a first sol, the tetraethyl orthosilicate, deionized water, hydrochloric acid and ethanol are mixed, a secondary reaction is performed, and then aging is performed to obtain a second sol, the first sol and the second sol are mixed, and then APG1214 and PVA are added to obtain a mixed solution, and the mixture is stirred to obtain a surface layer solution;

[0013] S4: coating treatment:

[0014] The glass substrate is cleaned with deionized water and isopropyl alcohol in sequence, and then the glass substrate is etched, and then the etched glass substrate is placed in a bottom layer solution, dip-coated for the first time, and then taken out and placed in an intermediate layer solution, dip-coated for the second time, and then taken out and calcined in a muffle furnace to obtain a glass plate with a bottom layer and an intermediate layer;

[0015] The glass plate having the bottom layer and the middle layer is placed in the surface layer solution for a third dip coating treatment, taken out and dried to obtain a high-performance coated AG glass.

[0016] Preferably, in step S1, the polyethylene glycol is one of polyethylene glycol 1000 and polyethylene glycol 2000; the usage ratio of tetraethyl orthosilicate, hydrochloric acid, deionized water, anhydrous ethanol and polyethylene glycol is (5-6) ml: (0.2-0.5) g: (1-2) ml: 50 ml: (0.2-0.5) g.

[0017] Preferably, in step S2, in the first solution, the usage ratio of tetraethyl orthosilicate, hydrochloric acid, deionized water, anhydrous ethanol and polyethylene glycol is (5-6) ml: (0.2-0.5) g: (1-2) ml: 50 ml.

[0018] Preferably, in step S2, in the second solution, the volume ratio of ammonia monohydrate to anhydrous ethanol is (7-8): (130-140).

[0019] Preferably, in step S2, in the third solution, the volume ratio of tetraethyl orthosilicate and anhydrous ethanol is (13-14): (60-70); in the intermediate layer solution, the volume fraction of the first solution is 5-6 v / v%.

[0020] Preferably, in step S3, in the preparation of the first sol, the molar ratio of tetraethyl orthosilicate, deionized water and ammonia monohydrate is (45-50):1:(3-5):(8-10); the temperature of the stirring reaction is 55-65°C and the time is 2-3h.

[0021] Preferably, in step S3, in the preparation of the second sol, the molar ratio of tetraethyl orthosilicate, deionized water, hydrochloric acid and ethanol is 1:1:(0.01-0.03):20, the temperature of the secondary reaction is 55-65°C, the time is 0.5-1.5h, and the aging time is 2-3d.

[0022] Preferably, in step S3, the usage ratio of the first sol, the second sol and the mixed solution is 5 g: (1-3) g: (30-50) ml.

[0023] Preferably, in step S4, when cleaning the glass substrate, the glass substrate is immersed in deionized water or isopropyl alcohol, and the immersion time is controlled to be 5-10 minutes; when etching, the glass substrate is immersed in piranha solution for 1-2 hours.

[0024] Preferably, in step S4, the conditions of the first dipping treatment, the second dipping treatment and the third dipping treatment are the same, the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time for each time is 100-120 s; and / or the calcination treatment temperature is 400-500° C., and the time is 1-3 h.

[0025] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0026] 1. The present invention sequentially coats a bottom layer solution, an intermediate layer solution and a surface layer solution on the surface of a glass substrate, and prepares different functional layers on the surface of the glass substrate. By optimizing the composition of each functional layer, the prepared glass not only has high light transmittance, but also has excellent anti-fog performance, adhesion performance, mechanical stability and solvent resistance, thereby improving the performance of the glass.

[0027] 2. The bottom layer solution of the present invention uses hydrochloric acid to catalyze the hydrolysis of tetraethyl orthosilicate. The condensation of tetraethyl orthosilicate plays a more active role than its condensation, and it is easier to guide the formation of linear chain silica sol, thereby preparing fibrous silica sol. The addition of polyethylene glycol can provide a porous structure during subsequent calcination, thereby forming an anchoring structure with the middle layer of spherical silica sol. Under the premise of ensuring high transmittance, the mechanical stability of the coating is improved. In addition, the fibrous silica sol can also be used as an adhesive to effectively improve the bonding performance between the coating and the glass substrate.

[0028] 3. In order to further improve the performance of coated glass, the present invention mixes the silica sol prepared by base catalysis with the silica sol prepared by acid catalysis, and adds a certain amount of APG1214 (dodecyl glucoside) and PVA, and the mixture of spherical silica sol and chain silica sol forms a composite nano-network composed of spherical nanoparticles and linear siloxane chains. This structure not only has excellent light transmittance, but also greatly increases the mechanical properties of the coating. The large amount of hydroxyl groups present in PVA and APG1214 effectively improve the hydrophilicity of the coating, thereby improving the anti-fog performance of the coating. DETAILED DESCRIPTION

[0029] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0031] Unless otherwise specified, the raw materials in the following examples and comparative examples are all commercially available, and the reaction conditions are all conventional conditions in the art unless otherwise specified.

[0032] Example 1

[0033] A method for preparing high-performance coated AG glass comprises the following steps:

[0034] (1) 5.3 mL of LTEOS, 0.4 g of hydrochloric acid, 2 mL of deionized water, and 50 mL of anhydrous ethanol were mixed, and then 0.2 g of polyethylene glycol 1000 was added and stirred for 5 h to obtain a bottom layer solution;

[0035] (2) 5.3 mL of tetraethyl orthosilicate, 0.4 g of hydrochloric acid, 2 mL of deionized water and 50 mL of anhydrous ethanol were mixed to obtain a first solution, 7.8 mL of ammonia monohydrate was mixed with 132 mL of anhydrous ethanol to obtain a second solution, 13.4 mL of tetraethyl orthosilicate was mixed with 66 mL of anhydrous ethanol to obtain a third solution, the second solution and the third solution were mixed and reacted until the pH of the system was neutral, and then the first solution was added to the reaction system and stirred to obtain an intermediate layer solution;

[0036] (3) Anhydrous ethanol, tetraethyl orthosilicate, deionized water and ammonia monohydrate were mixed in a molar ratio of 49:1:3:8, reacted at 60°C for 1 hour to obtain a first sol, tetraethyl orthosilicate, deionized water, hydrochloric acid and anhydrous ethanol were mixed in a molar ratio of 1:1:0.01:20, reacted at 60°C for 1 hour, aged for 3 days to obtain a second sol, 0.09g APG1214 and 0.5PVAg were dissolved in 100ml deionized water to obtain a mixed solution, and the first sol, the second sol and the mixed solution were mixed in a mass ratio of 5g:1g:30ml to obtain a surface layer solution;

[0037] S4: coating treatment:

[0038] The glass substrate is placed in deionized water and soaked at room temperature for 10 minutes, taken out and soaked in isopropanol for 10 minutes, taken out and soaked in piranha solution for 1.5 hours, taken out and dried, and then placed in the bottom solution for a dip coating treatment (the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time is 100 seconds), then taken out and placed in the middle layer solution for a second dip coating treatment (the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time is 100 seconds), taken out and calcined in a muffle furnace at 450° C. for 2 hours to obtain a glass plate having a bottom layer and a middle layer;

[0039] A glass plate having a bottom layer and an intermediate layer was placed in a surface layer solution for three dip coating treatments (the descending and ascending rates of the glass plate during immersion and removal were 1000 μm / s, and the immersion time was 100 s), and then dried after being taken out to obtain a high-performance coated AG glass.

[0040] Embodiment 2 A method for preparing high-performance coated AG glass comprises the following steps:

[0041] (1) 5.3 mL of LTEOS, 0.4 g of hydrochloric acid, 2 mL of deionized water, and 50 mL of anhydrous ethanol were mixed, and then 0.3 g of polyethylene glycol 1000 was added and stirred for 5.5 h to obtain a bottom layer solution;

[0042] (2) 5.3 mL of tetraethyl orthosilicate, 0.4 g of hydrochloric acid, 2 mL of deionized water and 50 mL of anhydrous ethanol were mixed to obtain a first solution, 7.8 mL of ammonia monohydrate was mixed with 132 mL of anhydrous ethanol to obtain a second solution, 13.4 mL of tetraethyl orthosilicate was mixed with 66 mL of anhydrous ethanol to obtain a third solution, the second solution and the third solution were mixed and reacted until the pH of the system was neutral, and then the first solution was added to the reaction system and stirred to obtain an intermediate layer solution;

[0043] (3) Anhydrous ethanol, tetraethyl orthosilicate, deionized water and ammonia monohydrate were mixed in a molar ratio of 49:1:3:8, and reacted at 60°C for 1.5 hours to obtain a first sol; tetraethyl orthosilicate, deionized water, hydrochloric acid and anhydrous ethanol were mixed in a molar ratio of 1:1:0.01:20, reacted at 60°C for 1 hour, and aged for 3 days to obtain a second sol; 0.09g APG1214 and 0.5PVAg were dissolved in 100ml deionized water to obtain a mixed solution; the first sol, the second sol and the mixed solution were mixed in a mass ratio of 5g:1g:40ml to obtain a surface layer solution;

[0044] S4: coating treatment:

[0045] The glass substrate is placed in deionized water and soaked at room temperature for 8 minutes, taken out and soaked in isopropanol for 8 minutes, taken out and soaked in piranha solution for 1 hour, taken out and dried, and then placed in the bottom solution for a dip coating treatment (the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time is 110 seconds), then taken out and placed in the middle layer solution for a second dip coating treatment (the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time is 110 seconds), taken out and calcined in a muffle furnace at 450° C. for 2.5 hours to obtain a glass plate having a bottom layer and a middle layer;

[0046] A glass plate having a bottom layer and an intermediate layer was placed in a surface layer solution for three dip coating treatments (the descending and ascending rates of the glass plate during immersion and removal were 1000 μm / s, and the immersion time was 110 s), and then dried after being taken out to obtain a high-performance coated AG glass.

[0047] Example 3

[0048] A method for preparing high-performance coated AG glass comprises the following steps:

[0049] (1) 5.3 mL of LTEOS, 0.4 g of hydrochloric acid, 2 mL of deionized water, and 50 mL of anhydrous ethanol were mixed, and then 0.35 g of polyethylene glycol 1000 was added and stirred for 5 h to obtain a bottom layer solution;

[0050] (2) 5.3 mL of tetraethyl orthosilicate, 0.4 g of hydrochloric acid, 2 mL of deionized water and 50 mL of anhydrous ethanol were mixed to obtain a first solution, 7.8 mL of ammonia monohydrate was mixed with 132 mL of anhydrous ethanol to obtain a second solution, 13.4 mL of tetraethyl orthosilicate was mixed with 66 mL of anhydrous ethanol to obtain a third solution, the second solution and the third solution were mixed and reacted until the pH of the system was neutral, and then the first solution was added to the reaction system and stirred to obtain an intermediate layer solution;

[0051] (3) Anhydrous ethanol, tetraethyl orthosilicate, deionized water and ammonia monohydrate were mixed in a molar ratio of 49:1:3:8, and reacted at 60°C for 2 hours to obtain a first sol; tetraethyl orthosilicate, deionized water, hydrochloric acid and anhydrous ethanol were mixed in a molar ratio of 1:1:0.01:20, reacted at 60°C for 1 hour, and aged for 3 days to obtain a second sol; 0.09g APG1214 and 0.5PVAg were dissolved in 100ml deionized water to obtain a mixed solution; the first sol, the second sol and the mixed solution were mixed in a mass ratio of 5g:1g:40ml to obtain a surface layer solution;

[0052] S4: coating treatment:

[0053] The glass substrate is placed in deionized water and soaked at room temperature for 10 minutes, taken out and soaked in isopropanol for 8 minutes, taken out and soaked in piranha solution for 2 hours, taken out and dried, and then placed in the bottom solution for a dip coating treatment (the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time is 120 seconds), then taken out and placed in the middle layer solution for a second dip coating treatment (the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time is 120 seconds), taken out and calcined in a muffle furnace at 450° C. for 3 hours to obtain a glass plate having a bottom layer and a middle layer;

[0054] A glass plate having a bottom layer and an intermediate layer was placed in a surface layer solution for three dip coating treatments (the descending and ascending rates of the glass plate during immersion and removal were 1000 μm / s, and the immersion time was 120 s), and then dried after being taken out to obtain a high-performance coated AG glass.

[0055] Example 4

[0056] A method for preparing high-performance coated AG glass comprises the following steps:

[0057] (1) 5.3 mL of LTEOS, 0.4 g of hydrochloric acid, 2 mL of deionized water, and 50 mL of anhydrous ethanol were mixed, and then 0.5 g of polyethylene glycol 1000 was added and stirred for 6 h to obtain a bottom layer solution;

[0058] (2) 5.3 mL of tetraethyl orthosilicate, 0.4 g of hydrochloric acid, 2 mL of deionized water and 50 mL of anhydrous ethanol were mixed to obtain a first solution, 7.8 mL of ammonia monohydrate was mixed with 132 mL of anhydrous ethanol to obtain a second solution, 13.4 mL of tetraethyl orthosilicate was mixed with 66 mL of anhydrous ethanol to obtain a third solution, the second solution and the third solution were mixed and reacted until the pH of the system was neutral, and then the first solution was added to the reaction system and stirred to obtain an intermediate layer solution;

[0059] (3) Anhydrous ethanol, tetraethyl orthosilicate, deionized water and ammonia monohydrate were mixed in a molar ratio of 49:1:3:8, and reacted at 60°C for 3 hours to obtain a first sol; tetraethyl orthosilicate, deionized water, hydrochloric acid and anhydrous ethanol were mixed in a molar ratio of 1:1:0.01:20, reacted at 60°C for 1 hour, and aged for 3 days to obtain a second sol; 0.09g APG1214 and 0.5PVAg were dissolved in 100ml deionized water to obtain a mixed solution; the first sol, the second sol and the mixed solution were mixed in a mass ratio of 5g:1g:50ml to obtain a surface layer solution;

[0060] S4: coating treatment:

[0061] The glass substrate is placed in deionized water and soaked at room temperature for 10 minutes, taken out and soaked in isopropanol for 10 minutes, taken out and soaked in piranha solution for 1.5 hours, taken out and dried, and then placed in the bottom solution for a dip coating treatment (the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time is 120 seconds), then taken out and placed in the middle layer solution for a second dip coating treatment (the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time is 120 seconds), taken out and calcined in a muffle furnace at 450° C. for 2.5 hours to obtain a glass plate having a bottom layer and a middle layer;

[0062] A glass plate having a bottom layer and an intermediate layer was placed in a surface layer solution for three dip coating treatments (the descending and ascending rates of the glass plate during immersion and removal were 1000 μm / s, and the immersion time was 120 s), and then dried after being taken out to obtain a high-performance coated AG glass.

[0063] In order to verify the effect of the present invention, the present invention is further described below with reference to Example 1 and in combination with a comparative example.

[0064] Comparative Example 1

[0065] Compared with Example 1, the difference is that the first dip coating process, the second dip coating process and the third dip coating process all use the bottom solution to coat the glass substrate, and the other conditions are the same as those in Example 1.

[0066] Comparative Example 2

[0067] Compared with Example 1, the difference is that the first dip coating process, the second dip coating process and the third dip coating process all use the intermediate layer solution to coat the glass substrate, and the other conditions are the same as those in Example 1.

[0068] Comparative Example 3

[0069] Compared with Example 1, the difference is that the first dip coating treatment, the second dip coating treatment and the third dip coating treatment all use the surface layer solution to coat the glass substrate, and the other conditions are the same as those in Example 1.

[0070] Comparative Example 4

[0071] Compared with Example 1, the difference is that the first dip coating process and the second dip coating process both use the bottom solution to coat the glass substrate, and the other conditions are the same as those in Example 1.

[0072] Comparative Example 5

[0073] Compared with Example 1, the difference is that: the first dip coating process and the second dip coating process both use the intermediate layer solution to coat the glass substrate.

[0074] Comparative Example 6

[0075] Compared with Example 1, the difference is that polyethylene glycol 1000 is not added to the bottom solution, and other conditions are the same as those in Example 1.

[0076] Comparative Example 7

[0077] Compared with Example 1, the difference is that an equal amount of the second sol is used in the surface layer solution to replace the first sol, and other conditions are the same as those in Example 1.

[0078] Comparative Example 8

[0079] Compared with Example 1, the difference is that an equal amount of the first sol is used to replace the second sol in the surface layer solution, and other conditions are the same as those in Example 1.

[0080] Comparative Example 9

[0081] Compared with Example 1, the difference is that the immersion time of the first immersion coating treatment, the second immersion coating treatment and the third immersion coating treatment during the coating treatment is 150 seconds, and the other conditions are the same as those in Example 1.

[0082] Comparative Example 10

[0083] Compared with Example 1, the difference is that the immersion time of the first immersion coating treatment, the second immersion coating treatment and the third immersion coating treatment during the coating treatment is 50 seconds, and the other conditions are the same as those in Example 1.

[0084] The performance tests of the materials prepared in the above embodiments and comparative examples are performed, and the test results are shown in Table 1, wherein the transmittance is tested within the visible light wavelength range, and the specific transmittance data is the average value within the visible light range.

[0085] Anti-fog performance test: After the glasses prepared in the examples and comparative examples were exposed to 80° C. water vapor for 30 seconds, their light transmittance was tested.

[0086] Adhesion test: The test was performed using a tape peeling test, where 3M 600-type transparent tape was applied to and removed from the coating surface for 70 cycles before observing the light transmittance of the coating.

[0087] Abrasion resistance test: After wiping the coating back and forth 300 times with a cotton cloth soaked in ethanol under a load of 500g, observe the light transmittance of the glass.

[0088] Solvent resistance test: The glasses prepared in the examples and comparative examples were immersed in water, 5 wt% H2SO4 aqueous solution, and isopropanol, respectively, and the solvent resistance time was calculated based on the fact that the transmittance did not decrease by 2%. Table 1

[0089]

[0090]

[0091]

[0092] It can be seen from the test results in Table 1 above that the present invention coats various functional layers on the glass surface and effectively adjusts the composition of each functional layer. The obtained coated glass not only has high light transmittance, but also has good anti-fog performance, strong adhesion, good mechanical stability and excellent solvent resistance.

[0093] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing high-performance coated AG glass, characterized in that: The following steps are involved: S1: Preparation of bottom solution: Mix ethyl orthosilicate, hydrochloric acid, deionized water and anhydrous ethanol, then add polyethylene glycol and stir to mix evenly to obtain a bottom solution; S2: Preparation of intermediate layer solution: Mixing tetraethyl orthosilicate, hydrochloric acid, deionized water and anhydrous ethanol to obtain a first solution, mixing ammonia monohydrate and anhydrous ethanol to obtain a second solution, mixing tetraethyl orthosilicate and anhydrous ethanol to obtain a third solution, slowly adding the third solution to the second solution to adjust the pH of the second solution to be neutral, and then adding the first solution to the second solution and mixing evenly to obtain an intermediate layer solution; S3: Preparation of surface solution: The tetraethyl orthosilicate, ethanol and deionized water are uniformly mixed, ammonia monohydrate is added, and a stirring reaction is performed to obtain a first sol, the tetraethyl orthosilicate, deionized water, hydrochloric acid and ethanol are mixed, a secondary reaction is performed, and then aging is performed to obtain a second sol, the first sol and the second sol are mixed, and then APG1214 and PVA are added to obtain a mixed solution, and the mixture is stirred to obtain a surface layer solution; S4: coating treatment: The glass substrate is cleaned with deionized water and isopropyl alcohol in sequence, and then the glass substrate is etched, and then the etched glass substrate is placed in a bottom layer solution, dip-coated for the first time, and then taken out and placed in an intermediate layer solution, dip-coated for the second time, and then taken out and calcined in a muffle furnace to obtain a glass plate with a bottom layer and an intermediate layer; The glass plate having the bottom layer and the middle layer is placed in the surface layer solution for a third dip coating treatment, taken out and dried to obtain a high-performance coated AG glass.

2. The method for preparing high-performance coated AG glass according to claim 1, characterized in that: In step S1, the polyethylene glycol is one of polyethylene glycol 1000 and polyethylene glycol 2000; the usage ratio of tetraethyl orthosilicate, hydrochloric acid, deionized water, anhydrous ethanol and polyethylene glycol is (5-6) ml: (0.2-0.5) g: (1-2) ml: 50 ml: (0.2-0.5) g.

3. The method for preparing high-performance coated AG glass according to claim 1, characterized in that: In step S2, in the first solution, the usage ratio of tetraethyl orthosilicate, hydrochloric acid, deionized water, anhydrous ethanol and polyethylene glycol is (5-6) ml: (0.2-0.5) g: (1-2) ml: 50 ml.

4. The method for preparing high-performance coated AG glass according to claim 1, characterized in that: In step S2, in the second solution, the volume ratio of ammonia monohydrate to anhydrous ethanol is (7-8): (130-140).

5. The method for preparing high-performance coated AG glass according to claim 1, characterized in that: In step S2, in the third solution, the volume ratio of tetraethyl orthosilicate and anhydrous ethanol is (13-14): (60-70); in the intermediate layer solution, the volume fraction of the first solution is 5-6 v / v%.

6. The method for preparing high-performance coated AG glass according to claim 1, characterized in that: In step S3, in the preparation of the first sol, the molar ratio of tetraethyl orthosilicate, deionized water and ammonia monohydrate is (45-50):1:(3-5):(8-10); the temperature of the stirring reaction is 55-65°C and the time is 2-3h.

7. The method for preparing high-performance coated AG glass according to claim 1, characterized in that: In step S3, in the preparation of the second sol, the molar ratio of tetraethyl orthosilicate, deionized water, hydrochloric acid and ethanol is 1:1:(0.01-0.03):20, the temperature of the secondary reaction is 55-65°C, the time is 0.5-1.5h, and the aging time is 2-3d.

8. The method for preparing high-performance coated AG glass according to claim 1, characterized in that: In step S3, the mass ratio of the first sol, the second sol and the mixed solution is 5g:(1-3)g:(30-50)ml.

9. The method for preparing high-performance coated AG glass according to claim 1, characterized in that: In step S4, when cleaning the glass substrate, the glass substrate is immersed in deionized water or isopropyl alcohol, and the immersion time is controlled to be 5-10 minutes; when etching, the glass substrate is immersed in piranha solution for 1-2 hours.

10. The method for preparing high-performance coated AG glass according to claim 1, characterized in that: In step S4, the conditions of the first dipping treatment, the second dipping treatment and the third dipping treatment are the same, the descending and ascending rates of the glass plate during immersion and removal are 1000 μm / s, and the immersion time for each time is 100-120 s; and / or the calcination temperature is 400-500° C., and the time is 1-3 h.